Improved diagnostics of purine and pyrimidine metabolism disorders using LC-MS/MS and its clinical application - Cremonesi, Alessio; Meili, David; Rassi, Anahita; Poms, Martin; Tavazzi, Barbara; Škopová, Václava; Häberle, Johannes; Zikánová, Marie; Hersberger, Martin (Clinical chemistry and laboratory medicine, 2023)
OBJECTIVES: To develop a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method to quantify 41 different purine and pyrimidine (PuPy) metabolites in human urine to allow detection of most known disorders in this metabolic pathway and to determine reference intervals. METHODS: Urine samples were diluted with an aqueous buffer to minimize ion suppression. For detection and quantification, liquid chromatography was combined with electrospray ionization, tandem mass spectrometry and multiple reaction monitoring. Transitions and instrument settings were established to quantify 41 analytes and nine stable-isotope-labeled internal standards (IS). RESULTS: The established method is precise (intra-day CV: 1.4-6.3%; inter-day CV: 1.3-15.2%), accurate (95.2% external quality control results within ±2 SD and 99.0% within ±3 SD; analyte recoveries: 61-121%), sensitive and has a broad dynamic range to quantify normal and pathological metabolite concentrations within one run. All analytes except aminoimidazole ribonucleoside (AIr) are stable before, during and after sample preparation. Moreover, analytes are not affected by five cycles of freeze-thawing (variation: -5.6 to 7.4%), are stable in thymol (variation: -8.4 to 12.9%) and the lithogenic metabolites also in HCl conserved urine. Age-dependent reference intervals from 3,368 urine samples were determined and used to diagnose 11 new patients within 7 years (total performed tests: 4,206). CONCLUSIONS: The presented method and reference intervals enable the quantification of 41 metabolites and the potential diagnosis of up to 25 disorders of PuPy metabolism.
Keywords: Purines; Chromatography, Liquid; stability; diagnosis; vysokoúčinná kapalinová chromatografie; Child; tandemová hmotnostní spektrometrie; dítě; Pyrimidines; puriny; purines; reprodukovatelnost výsledků; chromatografie kapalinová; Reproducibility of Results; Chromatography, High Pressure Liquid; LC-MS/MS; reference intervals; lidé; Humans; pyrimidiny; Tandem Mass Spectrometry; pyrimidines